2017
DOI: 10.1177/0886260517726971
|View full text |Cite
|
Sign up to set email alerts
|

Mediating Factors Explaining the Association Between Sexual Minority Status and Dating Violence

Abstract: Dating violence presents a serious threat for individual health and well-being. A growing body of literature suggests that starting in adolescence, individuals with sexual minority identities (e.g., individuals who identify as gay, lesbian, or bisexual) may be at an increased risk for dating violence compared with heterosexuals. Research has not, however, identified the mechanisms that explain this vulnerability. Using a diverse sample of young adults ( n = 2,474), the current study explored how minority stres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
39
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 44 publications
(42 citation statements)
references
References 57 publications
2
39
0
1
Order By: Relevance
“…This form of stigma relates to the negative ideas others hold about bisexual people, rather than bisexual people's internalization of these ideas. This finding is consistent with other research that has found bisexual stigma perpetuated by gay and lesbian people as well as heterosexual people is related to increased reports of sexual violence among bisexual women , and that discrimination mediates the relationship between bisexual identity and increased rates of dating violence among young adults (Martin-Storey & Fromme, 2017).…”
Section: Stigma Perpetuated By Otherssupporting
confidence: 92%
“…This form of stigma relates to the negative ideas others hold about bisexual people, rather than bisexual people's internalization of these ideas. This finding is consistent with other research that has found bisexual stigma perpetuated by gay and lesbian people as well as heterosexual people is related to increased reports of sexual violence among bisexual women , and that discrimination mediates the relationship between bisexual identity and increased rates of dating violence among young adults (Martin-Storey & Fromme, 2017).…”
Section: Stigma Perpetuated By Otherssupporting
confidence: 92%
“…En effet, des recherches antérieures suggèrent que les personnes « bisexuelles » et « principalement hétérosexuelles » éprouvent des facteurs de stress uniques par rapport à leurs homologues « homosexuelles » (Persson et coll., 2015 ;Petterson et coll., 2017 ;Talley et coll., 2016). En effet, les personnes « bisexuelles » indiquent des niveaux plus élevés de discrimination et éprouvent le rejet, à la fois, de certaines communautés de minorités sexuelles et des communautés hétérosexuelles (Martin-Storey et Fromme, 2017 ;Saewyc et coll., 2009). Ces expériences, à leur tour, peuvent expliquer leur plus grande vulnérabilité en matière de santé mentale.…”
Section: Discussionunclassified
“…Therefore, binegativity may elicit drinking to cope motives which may result in greater alcohol problems. In a seminal study of lesbian and bisexual women, discrimination mediated the relationship between sexual minority status (lesbian or bisexual) and dating violence for bisexual women; however, alcohol use was not a significant mediator (Martin-Story & Fromme, 2017). The association between discrimination and dating violence was not significant for lesbian women.…”
Section: The Contribution Of Binegativity To Sexual Coercionmentioning
confidence: 95%